2022
DOI: 10.4314/ahs.v22i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of definitive histopathological results of patients diagnosed with endometrial polyps: a tertiary care center experience

Abstract: Objectives: To determine the premalignancy and malignancy prevalence in patients diagnosed with endometrial polyps and to investigate factors affecting premalignancy and malignancy. Methods: In our retrospective study, patients who were diagnosed with endometrial polyp with endometrial samples and who underwent polypectomy by hysteroscopy or hysterectomy within one year were included. Results: Premalignant / malignant histopathological results were detected in 7 (2.8%) patients. There were no stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Normal and atrophic endometrium was observed in 37.3% of cases, while endometrial hyperplasia was observed in 54.2% and endometrial polyps in 6.8%. These results are in line with previous studies that have reported a higher incidence of benign results in women with postmenopausal bleeding (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%
“…Normal and atrophic endometrium was observed in 37.3% of cases, while endometrial hyperplasia was observed in 54.2% and endometrial polyps in 6.8%. These results are in line with previous studies that have reported a higher incidence of benign results in women with postmenopausal bleeding (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%